ZIS (Zakat, Infaq And Alms) Funds Management Methods In Improving The Quality Of Mustahiq Life In BAZNAS Karanganyar - Darlin Rizki (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: This study aims to analyze the role of philanthropy (ZIS) in reducing poverty and improving the quality of life in the Karanganyar society district.Method: This type of research is field research using a qualitative descriptive approach and applying an intrinsic case study model. The research data was obtained from the annual report of BAZNAS Karanganyar, interviews, and field observations as well as literature study conducted as secondary data.Findings: The results of this study found that ZIS can solve various problems and contribute to improving the quality of life of the Karanganyar community. Through the collaboration of BAZNAS with the city government, there are more than 600 UPZs scattered to collect zakat in government agencies, private companies, and the community. ZIS is realized in 5 flagship programs of BAZNAS Karanganyar, which can encourage productivity (being) and simultaneously increase mustahik's participation in their environment, such as family, social, workplace, school, and so on. And mustahik have hope and optimism to improve the quality of life (becoming).Originality/Values: Provide information to the public how ZIS management methods in BAZNAS Karanganyar, relationships with the city government, and the synergy of BAZNAS programs to improve the quality of  mustahik.life